Kepemimpinan Berdasarkan Kecerdasan Emosional Di MA Yayasan Pondok Karya Pembangunan Sentani - Dita Gunawan W (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Leadership with high EQ will be able to motivate themselves, then resonate with those around them. For a leader, emotional intelligence is an absolute requirement. Again, it is very unfortunate that our education is poor in concepts in helping to develop emotional intelligence (EQ), for students and university students. EQ training is essential to foster a dialogical, democratic, and participatory climate because all require emotional maturity in understanding and accepting differences. Ethnic, religious, and cultural plurality will become a source of latent conflict if it is not accompanied by the growth of dialogical culture and empathy. Research on Leadership Based on Emotional Intelligence at MA Yayasan Pondok Karya Pembangunan Sentani is a type of qualitative research, namely research that is not only ambitious to collect data in terms of quantity, but also wants to gain a deeper understanding of the phenomena that have been recorded. For example, exploring whether or not leaders are effective based on emotional intelligence (EQ). The results found that the Head of Madrasah MA Yayasan Pondok Karya Pembangunan Sentani was able to be firm and authentic, able to talk openly about his emotions or beliefs about the vision that guided them. They are receptive to constructive criticism and feedback, they also know when to ask for help and where to focus on growing new strengths.